Fundusz Inwestycyjny Inicjatywy Trójmorza: geneza i etapy rozwoju - Orzelska-Stączek, Agnieszka (Studia Polityczne, 2023)
The article aims to examine what the Three Seas Initiative Investment Fund is, how it was created and developed, and what are its connections with the Three Seas Initiative. Three stages of the Fund’s development have been distinguished: 2017–2018: the period from the emergence of the concept to the signing of the letter of intent to establish the fund; 2018–2020: fine-tuning the legal and financial framework; from 2020, in which the fund, as a new investment entity, began its commercial operations. In each of the three indicated stages, the relationship between the fund and the Three Seas Initiative developed differently. In the first and second stages, the fund was a concept whose implementation depended on the state of cooperation under the Three Seas Initiative. It was treated as a potential subsidy instrument, but over time this concept has changed. In the third stage, the fund became an independent legal entity, registered under Luxembourg law, with its statute, authorities and seat. While the Three Seas Initiative remains a loose form of cooperation, the fund is a clearly defined legal entity. It is intended to increase investment in Central Europe and generate profits for investors on a commercial basis. The Three Seas Fund is a different entity from the perspective of investors in the legal and financial dimension than for researchers of international relations. The Fund’s activity in the investment field affects cooperation under the Three Seas Initiative.